História da regulação jurídica da imigração no Império Brasileiro (1822-1889) - Silva Júnior, Edison Botelho (2025)
This doctoral thesis aims to examine the historical legal regulation of immigration, immigrants and foreigners during the period of the Brazilian monarchy, between 1822 and 1889. This demonstrates that there was a special legal system on immigration, with materially coherent correlations, built by a web of articulated rules, the changes of which followed the logic of political movements and the interests of the government and the established powers. The general objective was to understand the development of the early days of immigrant regulation in Brazil, based on an examination of the behavior of legislative and normative activity during the monarchical phase of government. The pillars of this thesis are the analysis of the following points: the general issues of Brazilian monarchical law, starting with the political integration brought about by the transfer of the Portuguese Court to Brazilian territory in 1808; the legal status of foreigners in their main elements, including their situation within the legal system, with special attention to registration and passports; the regulation of immigration and colonization and its phases, highlighting the impacts of political moments on legislative and normative formulation; contractual law imposed on immigrants; and the development of rules on naturalization. The thesis examined the laws, norms and rules created by the government, these being the primary sources, with the help of bibliographical sources that contextualize the development of immigration law. The examination of legal texts, their normative interconnections and their social contexts is the procedure followed in the development of the research and writing, which took place in the line of “Culture, Migrations and Work” of the Postgraduate Program in History of the Federal University of Santa Maria. With this, it constituted an innovative research, both for the transdisciplinary content and for the methodology and result, which brought a systematic examination of the laws and norms that regulated immigration, through the clash of powers that commanded public policies in the Brazilian Empire.